Afmeting excl. passe-partout. . "Titel prent: Onbluschbaar vuur : "Had ik nou het deksel er maar op!" - Hahn, Albert
Afmeting excl. passe-partout. "Titel prent: Onbluschbaar vuur : "Had ik nou het deksel er maar op!"